Investment, current account and the long swings of employment - Hian Teck Hoon; Margarita Katsime; Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2018)
We estimate the relationship between investment and unemployment over the time period 1960-2015 in 20 OECD countries. While neoclassical growth theory typically assumes full employment – with no effect of investment on unemployment – we find that over our sample period covering more than five decades, a statistically significant negative relationship does exist: when investment fell, unemployment increased. When the time period is broken down into two sub-periods to take account of the Great Recession, we find that the estimated coefficient of investment is slightly smaller when the period 2001-2015 is added to the 1960-2000 period. We also find a positive effect of the current account surplus on unemployment that very likely works through investment. A non-monetary model shows how an increase in policy uncertainty that sharply contracts investment and raises unemployment can lead to an increase in current account surplus.
Keywords: E10; E22; E24; 330; Long swings of unemployment; investment; current account; Great Recession; Investition; Leistungsbilanz; Arbeitslosigkeit; Weltwirtschaftskrise; OECD-Staaten